SIGNOS EM ATIVIDADES DE MODELAGEM MATEMÁTICA: MATEMATIZAÇÃO E RESOLUÇÃO EM FOCO - Gregório, Dallan Marcelo (2019)
Theoretical and Methodological aspects associated to Math Modeling in Mathematical Education have promoted intense reflection, debates and productions in the academic environment, specially linked to Post Graduation Programs, Research Groups and scientific events. However, associations between Math Modeling in the Mathmatics perspective and Semiotics are more restricted and limited if we consider its implementation in Basic Education. This way, the present paper tried to investigate what signs reveal when associated to the phases of Mathematization and Resolution proposed by Almeida, Silva e Vertuan (2012), in an activity of math modeling, from a study led with High School students in a private school in União da Vitória/PR, along the bimester mathematic lessons in which the researcher was also the professor of the reffered class. Math Modeling was used as a pedagogical alternative of teaching, through which students could investigate subjects of their interest and access mathematical and extra mathematical contents. For the implementation of activities, Almeida e Dias’ (2004) orientation was followed, regarding students’ familiarization to modeling activities, two being focused by now. We understand that the Mathematization and Resolution phases were successful regarding knowledge beyond mathematicians and this manifestation was effected through distinct signs. In order to analyze them, we chose the Semiotic Theory of Pierce. We framed the research in the qualitative paradigm, being the treatment and the analysis of the collected data anchored under the premises of the Content Analysis, by Lawrence Bardin (1977). We grouped the considerations in three dimensions: teaching, learning and scholar culture and have concluded, finally, that the identified signs reveal strategies of action and organization of data, language transitions, fossilized or not understood knowledge as well as difficulties regarding math symbology. Therefore, signs reveal important elements that influence the process of teaching and learning.